The use of space laser technology to develop the laser pulses system for the removal of space debris - Al - Osairy, Mohammed (Journal of natural sciences, life and applied sciences, 2017)
Several ideas we have been suggested to processing the problem of space debris, which pose a threat to the earth on the one hand and space missions and satellites on the other. From these ideas what is logical and practical and can be implemented today, and another what is elusive. From these practical scientific studies research on the use of laser technology by sending high-intensity pulses to change the debris path and prevent collisions. These studies have varied between the proposal to send these pulses from earth or space. This research focuses on the use of space laser technology and identifies the weaknesses of this technique and provides the idea of avoiding the weaknesses through the use of LADAR system to help determine the dimensions and speed of space objects and their components, which contributes to improving the method of processing and providing data on debris and development of treatment to include even natural space objects that pose a threat to earth as asteroids.